The use of urodynamic studies for the followup of neurogenic bladders treated with onabotulinumtoxinA - Bergeron, Michelle (Can Urol Assoc J, 2018)
INTRODUCTION: Intradetrusor injection of onabotulinumtoxinA (BoNTA) is well-established as treatment for patients with neurogenic bladders. Urodynamics (UDS) is used at regular intervals during followup to monitor intravesical pressure. With regards to the discomfort and risks associated with UDS, our objective was to assess if UDS done at regular intervals in the followup of neurogenic bladders treated with BoNTA had an impact on management. METHODS: We retrospectively analyzed the medical records of adult patients with neurological disorders treated with BoNTA for either detrusor overactivity or low bladder compliance at the Institut de Réadaptation en Déficience Physique de Québec (IRDPQ). At our centre, UDS was routinely performed at baseline, three months after the first treatment, then three months after every fifth set of injections. RESULTS: We identified 57 patients with neurological disorder treated with intravesical BoNTA. Each patient had between one and 19 sets of injections (mean 5.61 injections) and 1–6 followup UDS (mean 2.09). Of the 119 followup UDS reviewed at our centre, three UDS (2.5%) resulted in a modification of the urinary tract management from BoNTA to bladder augmentation. Two regimens were suspended and one was ended due to patient preference. CONCLUSIONS: Our study showed that UDS at pre-set intervals for followup of patients receiving BoNTA injections were rarely associated with modifications in the treatment course. Therefore, UDS should only be performed in cases where there are changes in the patient’s symptoms or if the urologist suspects that the treatment response is suboptimal.